A simple chemical approach to regenerating the strength of thermally damaged glass fibre. (November 2017) - Bashir, S.T.; Yang, L.; Anderson, R.; Tang, P.L.; Liggat, J.J.; Thomason, J.L.
Abstract: Process-induced strength loss is a major technical barrier to the effective reuse of thermally recycled glass fibres in composite applications. We have developed a novel approach to effectively restore strength in glass fibres through treatment in alkaline solutions. Glass fibres were treated at elevated temperature and experienced significant strength loss found typically after thermal recycling processes. Different alkaline treatments were then applied to the thermally damaged fibres in an attempt to restore strength which had been lost as a result of the heat conditioning procedure. Results indicated that these treatments were able to generate considerable fibre strength recovery. The degree of strength regeneration was found to be highly dependent on reaction conditions, which were investigated and optimised. The positive effect of these simple chemical treatments demonstrated great potential for facilitating the reuse of thermally recycled glass fibres in composite applications.